Técnicas de revegetação em uma zona ripária no município de Campo Verde, Mato Grosso - Novais, João Marcos Pereira (2018)
With the "New Brazilian Forest Code", revegetation of the deforested riparian zones has become mandatory, which does not meet the standards as of its validity. As riparian zones have important hydrological and ecological functions, the objectives of this work were to determine three revegetation techniques, based on their contributions to the soil attributes and native species of the Cerrado in a riparian zone. The restoration techniques (T) used in the degraded areas were: T1, seeds of native species incorporated into the soil; T2, fallow followed by planting native seedlings; T3, sowing of native seed mix, followed by planting of native seedlings; and T0, an adjacent reference area with native Cerrado vegetation. It was verified, after the survey of the plants undergoing regeneration, that T1 was the technique with the closest ecological indexes of T0, being: species richness (H '= 2.07) and floristic diversity (J' = 0.78). In addition, in T1 there was a dominance of species native to the cerrado. Regarding the soil attributes, it was observed that the total organic carbon stock (ECOT) and the nonlabile carbon stock (ECO n-lip) correlated strongly with the cation exchange capacity (CEC), soil organic matter (SOM) and with the sand stock. On the other hand, the labile carbon stock (ECO labile) correlated strongly with CEC, with sand, silt and clay stock and with the oxidized soil fractions. SOM contributed to the increase of CEC in all techniques, mainly in the superficial horizons, whereas, by means of the burning, there was a reduction in more than half the CEC in the superficial horizons. The T2 and T3 stored the largest amount of total organic carbon (TOC) per hectare at the depth of 0.30 m, and T1 presented intermediate storage between T2 and T3. The native Cerrado area (T0) was the one with the lowest storage. The recommended restauration technique for similar soil and climatic conditions is the sowing of native seeds incorporated into the soil. The areas with an agricultural production system using Brachiaria brizantha as pasture are efficient in reducing CO2 (g), however, it is not recommended for restauration of riparian zones.